How do we Know if Social Enterprise Works?: Tools for assessing social enterprise performance - Hall, Kelly; Arvidson, Malin (Social Enterprise, 2014)
Being able to demonstrate achievements and success has become an essential preoccupation for social enterprise organizations of today. How can such organizations know what they achieve? And how can they communicate this? These are challenging questions when applied to interventions aimed at delivering social and environmental impacts, and for organizations dealing with an array of stakeholders that may have very different views on how these impacts should be defined and evidenced. This chapter contributes to current debates about these and related questions held in the social enterprise community and among commissioners, grant-making bodies and social investors.